Water-based adhesive for chip multilayer ceramic capacitor and preparation method of water-based adhesive
By developing a specific water-based adhesive for the water-based casting forming process of sheet multilayer ceramic capacitors, the problems of particle wetting and blank quality are solved, and the feasibility of high-quality dielectric film preparation and industrial production is achieved.
Patent Information
- Application Number
- CN202510199113.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the water-based casting process of sheet multi-layer ceramic capacitors has problems such as difficult to ensure particle wettability, easy to cause defects and poor flexibility when the thin blank is dry, resulting in difficulty in applying it to industrial production.
An aqueous adhesive for sheet multilayer ceramic capacitors has been developed, which consists of polyvinyl alcohol, aqueous solvents, plasticizers, pH adjusters and modification aids. Through specific proportions and preparation methods, the wetting of the slurry particles and the quality of the dielectric film are ensured.
The feasibility of water-based casting is realized. The obtained dielectric film has good strength, flexibility and porcelain powder stacking density, avoiding the layering and cracking of the dielectric film during stacking and sintering, and reducing production costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of capacitor manufacturing, and in particular to a water-based adhesive for chip-type multilayer ceramic capacitors and a preparation method thereof. Background Art
[0002] In recent years, with the increasing degree of social informatization, electronic components have begun to develop in the direction of miniaturization, high frequency, broadband, high precision, integration and green environmental protection. As one of the basic components of electronic products, the use of chip multilayer ceramic capacitors has also increased rapidly. Chip multilayer ceramic capacitors are capacitors formed by connecting multiple single-layer capacitors in a stacked manner. They are composed of inner electrodes, dielectric materials, and terminal electrodes. The inner electrodes and ceramic dielectrics are alternately superimposed in parallel to form the main part of the chip multilayer ceramic capacitor. The terminal electrodes are generally three-layer structures. The innermost layer is the conductive phase powder, which serves to connect and lead out the inner electrode. The middle layer is a barrier layer to prevent the conductive phase from being corroded by the molten solder during welding. The outermost layer is a welding layer to ensure that the chip multilayer ceramic capacitor has good welding performance.
[0003] The main preparation methods for dielectric films of existing chip-type multilayer ceramic capacitors are screen printing, Soufill film and cast film, and the cast film method is the most widely used manufacturing method in industrial applications. The existing production process of preparing chip-type multilayer ceramic capacitors by cast film is as follows: slurry preparation → ceramic film casting → inner electrode film pattern screen printing → pattern cutting and peeling → stacking electrode pattern according to process requirements → capacitor lamination → capacitor cutting → capacitor sintering → terminal electrode → sintered electrode → electroplating → test sorting number → finished product. Among them, slurry configuration is the technical core of this field, which directly affects the quality of the dielectric film, and then affects the quality of the capacitor.
[0004] At present, in the existing technology, the production of dielectric films mainly adopts a non-aqueous cast molding process using polyvinyl butyral (PVB) as an adhesive; that is, the slurry is configured with PVB as an adhesive and an oily system is used. The dielectric film prepared by this process has high mechanical strength, good flexibility, relatively uniform structure, and is easy to cut and process later. However, the above process uses a large amount of organic matter (such as toluene) as a solvent when configuring the slurry, and uses a certain amount of additives (including organic dispersants, plasticizers, adhesives, etc.). These organic substances are toxic, flammable, and have odors, which will seriously pollute the environment.
[0005] The use of water-based tape casting, that is, the use of water-based system slurry configuration, using water instead of organic solvents as solvents, and using water-soluble polymer materials as adhesives, not only meets environmental protection requirements, but also reduces costs, and is the future development direction of this field. However, the use of water-based system slurry configuration faces some difficulties, such as the difficulty in ensuring the wettability of particles, the easy occurrence of defects when drying thin blanks, and the poor flexibility of thin blanks. Due to the existence of the above problems, water-based tape casting is currently difficult to apply to industrial production. Summary of the invention
[0006] In order to solve at least one of the above technical problems, a water-based adhesive that can be suitable for the slurry configuration of chip-type multilayer ceramic capacitors and can ensure the wettability of the slurry particles and the quality of the resulting dielectric film is relatively excellent is developed. The present application provides a water-based adhesive for chip-type multilayer ceramic capacitors and a preparation method thereof.
[0007] On the one hand, the present application provides an aqueous adhesive for chip-type multilayer ceramic capacitors, wherein the components of the aqueous adhesive for chip-type multilayer ceramic capacitors include: 8 to 10 parts of polyvinyl alcohol, 48 to 48 parts of an aqueous solvent, 8 to 10 parts of a plasticizer, 0.5 parts of a pH adjuster, and 1.5 parts of a modification aid; the degree of alcoholysis of the polyvinyl alcohol is 75 to 90%, and the degree of polymerization is 1000 to 2500.
[0008] Optionally, the aqueous solvent is deionized water or an aqueous solution of an alcohol compound.
[0009] Optionally, the plasticizer is polyethylene glycol with a molecular weight of more than 600.
[0010] Optionally, the plasticizer is a mixture of polyethylene glycol with a molecular weight of more than 600 and carboxyethyl cellulose, and the mass proportion of the polyethylene glycol in the mixture is 80-90%.
[0011] Optionally, the pH adjuster is an amine neutralizer.
[0012] Optionally, the modification aid includes a defoamer and a dispersant.
[0013] Further optionally, the defoaming agent is a water-based silicone defoaming agent, and the dispersant is an acrylic dispersion or triethanolamine.
[0014] Further optionally, the modification aid also includes a wetting agent and / or a release agent.
[0015] Further optionally, the wetting agent is propylene glycol or glycerol.
[0016] On the other hand, the present application provides a method for preparing the above-mentioned chip-type multilayer ceramic capacitor using an aqueous adhesive, comprising the following steps: S1. Fully mix the aqueous solvent, plasticizer, pH adjuster and modifying agent in the formulated amount to prepare a mixed solution; S2, adding the formulated amount of polyvinyl alcohol to the mixed solution obtained in step S1, heating the mixture to 85-95°C at a heating rate of 2-5°C under stirring conditions at a speed of 40-100 rpm, maintaining the above temperature conditions, continuing stirring for 1.5-2h, maintaining stirring conditions, and naturally cooling to room temperature to obtain a glue solution; S3. Stop stirring the glue solution obtained in step S3, and let it stand for 1 to 2 hours to remove bubbles, so as to obtain a water-based adhesive for chip-type multilayer ceramic capacitors.
[0017] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application uses polyvinyl alcohol and a water-washing solvent to prepare a water-based adhesive for use in the slurry preparation of chip-type multilayer ceramic capacitors. It can achieve water-based tape casting, and each raw material component is basically non-toxic and has minimal pollution to the environment.
[0018] 2. This application uses specific polyvinyl alcohol as the main component of the adhesive, supplemented by a specific ratio. The obtained adhesive can have good wettability to the slurry particles, and the obtained cast film has suitable strength, flexibility, and a large ceramic powder bulk density.
[0019] 3. The adhesive of the present application is used for preparing dielectric films by water-based tape casting, and the obtained tape casting film does not delaminate or crack during lamination; after debinding and sintering, the chip-type multilayer capacitor product does not delaminate or crack.
[0020] 4. The preparation method of the present application has simple steps, is easy to operate, and has low overall preparation cost. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] The present application provides an aqueous adhesive for chip-type multilayer ceramic capacitors. The components of the aqueous adhesive for chip-type multilayer ceramic capacitors include: 8 to 10 parts of polyvinyl alcohol, 48 to 48 parts of an aqueous solvent, 8 to 10 parts of a plasticizer, 0.5 parts of a pH adjuster, and 1.5 parts of a modification aid; the degree of alcoholysis of the polyvinyl alcohol is 75 to 90%, and the degree of polymerization is 1000 to 2500.
[0023] The method for preparing a chip-type multilayer ceramic capacitor using an aqueous adhesive of the present application comprises the following steps: S1. Fully mix the aqueous solvent, plasticizer, pH adjuster and modifying agent in the formulated amount to prepare a mixed solution; S2, adding the formulated amount of polyvinyl alcohol to the mixed solution obtained in step S1, heating the mixture to 85-95°C at a heating rate of 2-5°C under stirring conditions at a speed of 40-100 rpm, maintaining the above temperature conditions, continuing stirring for 1.5-2h, maintaining stirring conditions, and naturally cooling to room temperature to obtain a glue solution; S3. Stop stirring the glue solution obtained in step S3, and let it stand for 1 to 2 hours to remove bubbles, so as to obtain a water-based adhesive for chip-type multilayer ceramic capacitors.
[0024] Prior to this application, the existing technology for industrial and large-scale production of chip-type multilayer ceramic capacitors mostly used an oily slurry system. This was mainly because after the slurry was prepared, the ceramic powder was easy to disperse in the oily system and not easy to agglomerate. The cast film made using PVB as a binder had better quality.
[0025] The above oily system has environmental problems and relatively high costs. Based on the problems of the prior art, this application adopts a specific ratio to configure a new water-based adhesive, which can configure a water-based slurry system. The ratio of this application effectively solves the problem of insufficient dispersion and wetting of ceramic powder in the water-based system.
[0026] The following are examples of the present application: The main raw materials used in the examples of this application are commercially available.
[0027] The following are Examples 1 to 8 of the present application, and Examples 1 to 8 of the present application are all prepared using the following preparation method.
[0028] The method for preparing a chip-type multilayer ceramic capacitor using an aqueous adhesive according to an embodiment of the present application comprises the following steps: S1. Fully stir and mix the aqueous solvent, plasticizer, pH adjuster and modifying agent in the formulated amount to prepare a mixed solution; S2, adding the formulated amount of polyvinyl alcohol to the mixed solution obtained in step S1, heating to 90°C at a heating rate of 5°C under stirring at a speed of 60 rpm, maintaining the above temperature conditions, continuing stirring for 2 hours, maintaining the stirring conditions, and naturally cooling to room temperature to obtain a glue solution; S3. Stop stirring the glue solution obtained in step S3, and let it stand for 2 hours to remove bubbles, so as to obtain a water-based adhesive for chip-type multilayer ceramic capacitors.
[0029] The formulations of Examples 1 to 8 of the present application are shown in Table 1 below.
[0030] Table 1 Proportions of Examples 1 to 8
[0031] The polyvinyl alcohol used in Examples 1 to 4 of the present application has a degree of alcoholysis of 75% and a degree of polymerization of 1000. The polyvinyl alcohol used in Example 5 has a degree of alcoholysis of 80% and a degree of polymerization of 1500. The polyvinyl alcohol used in Example 6 has a degree of alcoholysis of 85% and a degree of polymerization of 2000. The polyvinyl alcohol used in Example 7 has a degree of alcoholysis of 90% and a degree of polymerization of 2500. The polyvinyl alcohol used in Example 8 has a degree of alcoholysis of 80% and a degree of polymerization of 2000.
[0032] The defoamer and dispersant used in Examples 1 to 8 of the present application are water-based silicone defoamer and acrylic dispersion respectively. The plasticizer used in Examples 1 to 8 of the present application is PEG800.
[0033] Comparative Example 1: The slurry configuration of Example 1 of the Chinese invention patent with publication number CN119028743A is used as Comparative Example 1 of the present application.
[0034] Comparative Example 2: This comparative example differs from Example 8 in that no plasticizer is added.
[0035] Comparative Example 3: This comparative example differs from Example 8 in that no modifying aid is added.
[0036] Detection: The adhesives of Examples 1 to 8 and Comparative Examples 2 to 3 of the present application were used to prepare slurries for chip-type multilayer ceramic capacitors, and the dispersibility and wettability of the slurries were tested.
[0037] The slurries prepared in Examples 1 to 8 and Comparative Examples 1 to 3 of the present application were cast on a steel belt to test the quality of the cast film.
[0038] Among them, the wettability adopts the contact angle with the ceramic powder pressing plate as the detection index; the slurry dispersion is determined by the fineness index.
[0039] The test results are shown in Table 2 below.
[0040] Table 2 Test results of Examples 1 to 8 and Comparative Examples 1 to 3
[0041] From the data in Table 2, it can be seen that the adhesives of Examples 1 to 8 of the present application are configured with water-based slurries, and their wettability is slightly lower than that of the oil-based slurry of Comparative Example 1, but the slurry dispersion is relatively uniform, and the quality of the cast film obtained is almost at the same level as that of Comparative Example 1. The adhesives of Examples 1 to 8 of the present application are configured with water-based slurries, and their wettability and dispersibility are significantly better than those of Comparative Examples 2 and 3, and the quality of the cast film obtained is also significantly better than that of Comparative Examples 2 and 3.
[0042] It can be seen that the adhesive of the present application, which adopts specific polyvinyl alcohol and plasticizer, and is matched with a defoamer and a dispersant, is used for water-based slurry preparation, which can effectively promote the dispersion of ceramic powder and has good wettability to particles.
[0043] From the data in Table 2, it can be seen from the data comparison of Examples 1 to 8 that the polyvinyl alcohol of the present application uses a product with a degree of alcoholysis of 80 to 85% and a degree of polymerization of about 2000. The quality of the resulting adhesive is better, and both wettability and dispersibility are improved. The contact angle is within 9.8 degrees, which can basically ensure complete wetting of the ceramic powder.
[0044] The following are Examples 9 to 14 of the present application, which are based on Example 8 of the present application.
[0045] Example 9: The difference between this example and Example 8 is that PEG1000 is used as the plasticizer.
[0046] Example 10: The difference between this example and Example 8 is that an ethanol aqueous solution with a volume fraction of 40% is used as the aqueous solvent.
[0047] Example 11: The difference between this example and Example 8 is that 0.5 parts of propylene glycol is added to the adhesive.
[0048] Example 12: The difference between this example and Example 10 is that the plasticizer is a mixture of PEG1000 and carboxyethyl cellulose, and the mass proportion of PEG1000 in the mixture is 80%.
[0049] Example 13: The difference between this example and Example 10 is that the plasticizer is a mixture of PEG1000 and carboxyethyl cellulose, and the mass proportion of PEG1000 in the mixture is 90%.
[0050] Example 14: The difference between this example and Example 10 is that the plasticizer is a mixture of PEG1400 and carboxyethyl cellulose, and the mass proportion of PEG1000 in the mixture is 90%.
[0051] The same test was performed on Examples 9 to 14 of the present application, and the results are shown in Table 3 below.
[0052] Table 3 Test results of Examples 9 to 14
[0053] It can be seen from the data in Table 3 that the use of the composite plasticizer in the present application can not only improve the quality of the cast film, but also help to wetting and disperse the ceramic powder; in addition, among the plasticizers in the present application, polyethylene glycol is selected from products with a molecular weight of more than 1000, and the dispersibility and wettability of the prepared adhesive, as well as the quality of the cast film can be further improved.
[0054] The applicant has also conducted relevant experimental research on the preparation method of the present application. Within the process parameter range of the present application, the performance of the prepared adhesive does not differ much.
[0055] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A water-based adhesive for a chip-type multilayer ceramic capacitor, characterized in that: The components of the water-based adhesive used for the chip-type multilayer ceramic capacitor include: 8-10 parts of polyvinyl alcohol, 48-48 parts of aqueous solvent, 8-10 parts of plasticizer, 0.5 parts of pH adjuster, and 1.5 parts of modification aid; the alcoholysis degree of the polyvinyl alcohol is 75-90%, and the polymerization degree is 1000-2500.
2. The method for synthesizing magnesium L-threonate according to claim 1, characterized in that: The aqueous solvent is deionized water or an aqueous solution of an alcohol compound.
3. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 1, characterized in that: The plasticizer is polyethylene glycol with a molecular weight of more than 600.
4. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 1, characterized in that: The plasticizer is a mixture of polyethylene glycol with a molecular weight of more than 600 and carboxyethyl cellulose, and the mass proportion of the polyethylene glycol in the mixture is 80-90%.
5. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 1, characterized in that: The pH adjuster is an amine neutralizer.
6. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 1, wherein: The modification aids include defoamers and dispersants.
7. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 6, characterized in that: The defoamer is a water-based organosilicon defoamer, and the dispersant is an acrylic acid dispersion or triethanolamine.
8. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 6, characterized in that: The modification aids also include wetting agents and / or mold release agents.
9. The aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 8, characterized in that: The wetting agent is propylene glycol or glycerol.
10. A method for preparing an aqueous adhesive for a chip-type multilayer ceramic capacitor according to claim 1, characterized in that: The following steps are involved: S1. Fully mix the aqueous solvent, plasticizer, pH adjuster and modifying agent in the formulated amount to prepare a mixed solution; S2, adding the formulated amount of polyvinyl alcohol to the mixed solution obtained in step S1, heating the mixture to 85-95°C at a heating rate of 2-5°C under stirring conditions at a speed of 40-100 rpm, maintaining the above temperature conditions, continuing stirring for 1.5-2h, maintaining stirring conditions, and naturally cooling to room temperature to obtain a glue solution; S3. Stop stirring the glue solution obtained in step S3, and let it stand for 1 to 2 hours to remove bubbles, so as to obtain a water-based adhesive for chip-type multilayer ceramic capacitors.
Citation Information
Patent Citations
Preparation method of ceramic diaphragm and multilayer chip ceramic capacitor
CN119028743A